+0  
 
0
267
1
avatar

The second of two numbers is the first diminished my 6. Their sum is 12. Find the numbers.

 Dec 11, 2017

Best Answer 

 #1
avatar+7352 
+1

Let's call the first number  " f "  and the second number  " s " .   We know...

 

s  =  f - 6

                      and

s + f  =  12

 

Plug in   f - 6   for   s   into the second equation.

 

(f - 6) + f   =   12

2f - 6   =   12

2f   =   18

f   =   9               Use this value for  f  in the first equation to find  s  .

 

s   =   f - 6   =   9 - 6   =   3

 Dec 11, 2017
 #1
avatar+7352 
+1
Best Answer

Let's call the first number  " f "  and the second number  " s " .   We know...

 

s  =  f - 6

                      and

s + f  =  12

 

Plug in   f - 6   for   s   into the second equation.

 

(f - 6) + f   =   12

2f - 6   =   12

2f   =   18

f   =   9               Use this value for  f  in the first equation to find  s  .

 

s   =   f - 6   =   9 - 6   =   3

hectictar Dec 11, 2017

24 Online Users

avatar
avatar
avatar
avatar